Genetic composition of Atlantic and Mediterranean recruits of European eel Anguilla anguilla based on EST-linked microsatellite loci - Pujolar, JM; De Leo, GA; Zane, L.; CICCOTTI, ELEONORA (Journal of Fish Biology, 2009)
Anguilla anguilla glass eels arriving at two Mediterranean and two Atlantic sites were tested for differences in genetic composition between regions using a total of 23 microsatellite loci developed from an expressed sequence tag (EST) library. Hierarchical analysis of molecular variance indicated a non-significant difference between regions (Mediterranean v. Atlantic), which contrasted with the significant differences observed between samples within regions. The existence of a single spawning site for all A. anguilla individuals and extensive migration loop with great opportunity for mixing of individuals might explain the homogeneity in genetic composition found between regions. The observation of a (small-scale) pattern of genetic patchiness among intra-annual samples (arrival waves) within geographic regions does not conflict with the lack of (large-scale) geographic substructuring found between the Mediterranean and Atlantic regions, but most likely is a consequence of the strong dependence of A. anguilla on oceanic conditions in the Sargasso Sea that might result in a limited parental contribution to each spawning event. The comparison of Atlantic and Mediterranean A. anguilla glass eel recruits based on EST-linked microsatellite loci provides evidence supporting the hypothesis of panmixia A. anguilla across Europe.